The Role of Small and Medium - sized Enterprises to Promote Halal Tourism: The Case of Indonesia - HENDIJANI, Roozbeh BABOLIAN; SANNY, Lim (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021, 2021)
Purpose - The tourism industry on a global scale has become a competitive market and knowing about the experience of tourists plays an important role in destination development. One of the growing segments in the tourism industry is halal tourism. The competitiveness of Indonesia as the most country with the largest Muslim population demonstrates a need for improvement at promoting halal tourism. This study planned to find out the role of different factors such as amenities, access and attraction on the satisfaction and intention to visit of Muslim tourists. Design – The outcomes determined important attributes which can be useful for SMEs, destination marketers and stakeholders in Indonesia to have a better marketing strategy for promoting halal tourism. Methodology - A quantitative approach was used where self-administrated questionnaires were distributed among Muslim inbound tourists in Jakarta, Indonesia. Statistical analysis such as descriptive analysis, simple and multiple linear regression were used to analyze the collected data. Findings - The results of this study found ‘amenities’ significantly affected the satisfaction of Muslim tourists who visited Indonesia and there was a significant relation between satisfaction and intention to revisit this country. Originality - This research was one of the few to assess the importance of SMEs to promote halal tourism in Indonesia.